Two new titles in 'The Tropical Agriculturalist' series 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Field surveying for land and water management Agrodok books are distributed free to nationals of ACP countries: for details write to CTA.